Efecto de Trichoderma spp. aislados del distrito de Santiago de Cao sobre huevos de Melodoigyne sp. en condiciones de laboratorio y de invernadero - LOPEZ FUENTES, Fiorella Lisset (2019)
In order to reduce the use of chemical pesticides that produce high toxicity and damage the ground, it is necessary to look for ecological alternatives, using biological controllers such as fungi, to treat diseases and blight that affect to the plants, especially, the underground part without leaving polluting residues. For this reason, the objective of this research work is to know the effect of the native crops of Trichoderma sp., isolated from the district of Santiago de Cao on eggs of Meloidogyne sp. in laboratory conditions. These pure crops were isolated and selected three crops native Trichoderma sp. (TSCL2, TSCS2, TSCZ2), due to its greater radial growth and amount of conidia/mL. Thirty Lycopersicum esculentum plants were used, which were distributed in six groups and received different treatments for two months. After the treatment period, the plants of L. esculentum were extracted by calculating the percentage of Root nodulations and percentage of root weight, these results were processed applying the variance analysis test ANOVA and the Tukey test, finding significant differences between the treatments in both results. For this reason, it is concuted that the threecultures of Trichoderma spp. native selected and evaluated have a biocontrol effect on Meloidogyne sp. eggs, but the TSCL2 native crops has the lowest percentage of nodulation and a higher percentage of root weight.